2021
DOI: 10.1111/joor.13245
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of macrophages in the trigeminal ganglion of rats with pulpitis

Abstract: Background Dental pulp tissues are rich in pain‐related afferent nerve fibers, which originate from primary sensory neurons in the trigeminal ganglion (TG). The mechanisms of central nervous system (CNS) underlying ectopic pain following peripheral inflammation have been reported that the macrophages as inflammatory and immunologic mediators in the TG play an important role in the process of pulpitis and hyperalgesia. Objective(s) To observe the polarization response and dynamic distribution of macrophages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…This result is consistent with those observed in previous studies. 5,55,56 Minimal changes were observed between sympathectomy and sham surgery group before CFA treatment, suggesting sympathectomy has no significant effect on macrophage phenotypic transition. Prior sympathectomy significantly reduced M1 macrophage infiltrated in TG from 1 to 14 dpi, suggesting that the SNS may promote M1 polarization in the TG during orofacial inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…This result is consistent with those observed in previous studies. 5,55,56 Minimal changes were observed between sympathectomy and sham surgery group before CFA treatment, suggesting sympathectomy has no significant effect on macrophage phenotypic transition. Prior sympathectomy significantly reduced M1 macrophage infiltrated in TG from 1 to 14 dpi, suggesting that the SNS may promote M1 polarization in the TG during orofacial inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…The enhanced M1 polarization would exacerbate pulpitis progression [27], while M2 macrophages exerted a pivotal impact on the attenuation of reversible pulpitis and recovery of pulp tissue [28]. Concentrating on the relationship between macrophage phenotypes and nerve regeneration, Gao et al [29] found that in the early acute stage of pulpitis, the ratio of M2 to M1 macrophages was considerably reduced in trigeminal ganglion. However, as pulp inflammation subsided, this ratio was reversed entirely, indicating that the phenotypic transformation of macrophages from M1 to M2 facilitated nerve repair in pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PPARγ has been linked to reduction in neuroinflammation via microglia in models of neuropathic pain [19]. Importantly, recent research has demonstrated that macrophages and microglia participate in neuroinflammation in the trigeminal ganglia following pulp exposure, suggesting that this may play a critical role in the development of inflammatory pain associated with pulpitis [20]. The present study does not investigate the receptor mechanism involved in the β-CP suppression of AIF gene expression; however, mounting evidence suggests that CB2 receptor/PPARγ cross-talk is the critical target for β-CP's antiinflammatory effects [21].…”
Section: Discussionmentioning
confidence: 99%